Length Weight Relationships of Marine Ornamental Fish Threespot Humbug Dascyllus trimaculatus Ruppell 1829 from Gulf of Mannar South East Coast of India - Priyadharsini, S (International Journal of Pharmaceutical & Biological Archive, 2012)
Length Weight Relationships of Marine Ornamental Fish Threespot Humbug Dascyllus trimaculatus Ruppell 1829 from Gulf of Mannar South East Coast of India